2020
DOI: 10.1038/s41467-020-15259-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein-polymer bioconjugates via a versatile oxygen tolerant photoinduced controlled radical polymerization approach

Abstract: The immense application potential of amphiphilic protein-polymer conjugates remains largely unexplored, as established "grafting from" synthetic protocols involve time-consuming, harsh and disruptive deoxygenation methods, while "grafting to" approaches result in low yields. Here we report an oxygen tolerant, photoinduced CRP approach which readily affords quantitative yields of protein-polymer conjugates within 2 h, avoiding damage to the secondary structure of the protein and providing easily accessible mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
112
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 72 publications
2
112
1
Order By: Relevance
“…Photoirradiation of a copper catalyst in the presence of an electron donor in excess enables removal of dissolved oxygen. [42][43][44][45][46][47][48][49][50][51][52][53][54] Despite these great developments, the vast majority of reported methods are successful only when polymerization is performed in sealed vessels with a limited amount of oxygen in the reaction mixture. So far, only a few ATRP systems, mainly based on enzymatic degassing, can be carried out in a completely open reaction vessel, where oxygen continuously diffuses into the system from the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Photoirradiation of a copper catalyst in the presence of an electron donor in excess enables removal of dissolved oxygen. [42][43][44][45][46][47][48][49][50][51][52][53][54] Despite these great developments, the vast majority of reported methods are successful only when polymerization is performed in sealed vessels with a limited amount of oxygen in the reaction mixture. So far, only a few ATRP systems, mainly based on enzymatic degassing, can be carried out in a completely open reaction vessel, where oxygen continuously diffuses into the system from the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent publication showed that proteins such as glucose-oxidase can be modified with polystyrene to the point of becoming globular nanoparticles, with improved or retained activity. 11 Recent work on surface-immobilization of enzymes has shown that lipase catalytic performance can be dramatically improved by attachment to hydrophilic surface-grafted polymers. 12 In a subsequent publication, by the same group, it was found that there is a trade-off in this system – more protein–polymer attachments resulted in higher stability but lower activity due to decreased motion in the folded state of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that Cu-RDRP has been considered as one of the most robust strategies due to successful implementation under various conditions (e.g. in the presence of oxygen/air, [13][14][15] in various reaction media [16][17][18] ) and also due to the wide of range of materials that can be synthesized (i.e. polyacrylates, polymethacrylates, polystyrene, polyacrylamides) with excellent control over their (macro)molecular characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main advantages of Cu-RDRP is its successful implementation in aqueous media, with excellent control over the macromolecular characteristics of the synthesized polymers. 15,18,19,21,30,31 In the presence of multidentate aliphatic amine ligands (e.g. tris [2-(dimethylamino)ethyl]amine, Me 6 TREN) and in aqueous media, Cu(I) is highly unstable towards rapid disproportionation, leading to Cu(II) and nascent, highly active Cu(0).…”
Section: Introductionmentioning
confidence: 99%